ANALISIS KESENJANGAN TABUNGAN-INVESTASI BERDASARKAN RESIDUAL MODEL: STUDI KASUS ASEAN-4 - Pasaribu, Syamsul Hidayat (Journal of Indonesian Economy and Business, 2003)
This paper attempts to explain and estimate the two-gap analysis in terms of capitalmobility by residual of econometric models. The research presents the cases of ASEAN-4(Indonesia, Malaysia, Philippines and Thailand). The two-gap analysis is an identity and itcannot be estimated by the econometric method. For the purposes of this research, first the identity is modified in econometric models. Second, then the modified models could beestimated.Estimating identity with econometric model has at least two advantages. (1) Theresidual of econometric model could be interpreted as the variables that are not allowed inthe model. (2) The residual of econometric model is minimized, so the residual model interm of this research could be interpreted as minimum value of the government or privatesaving-investment gap.The results show the models that have been modified in econometric models can capturethe identity of two-gap analysis. The better estimated models to explain the capital mobility of those countries are the private saving-investment gap models, except for Indonesian case. Moreover, the residuals of the private saving-investment gap models can capture the estimated values of the government saving-investment gaps, especially in the cases of Malaysia, Philippines, and Thailand.Keywords: two-gap analysis; saving-investment gap; ordinary least squares; errorcorrection model.